Methotrexate Treatment of Newly Diagnosed RA Patients Is Associated With DNA Methylation Differences at Genes Relevant for Disease Pathogenesis and Pharmacological Action - Guderud, Kari; Sunde, Line H.; Flåm, Siri T.; Mæhlen, Marthe T.; Mjaavatten, Maria D.; Norli, Ellen S.; Evenrød, Ida M.; Andreassen, Bettina K.; Franzenburg, Sören; Franke, Andre; Rayner, Simon; Gervin, Kristina; et al. (Frontiers in Immunology, 2021)
Background Methotrexate (MTX) is the first line treatment of rheumatoid arthritis (RA), and methylation changes in bulk T cells have been reported after treatment with MTX. We have investigated cell-type specific DNA methylation changes across the genome in naïve and memory CD4+ T cells before and after MTX treatment of RA patients. DNA methylation profiles of newly diagnosed RA patients (N=9) were assessed by reduced representation bisulfite sequencing. Results We found that MTX treatment significantly influenced DNA methylation levels at multiple CpG sites in both cell populations. Interestingly, we identified differentially methylated sites annotated to two genes; TRIM15 and SORC2, previously reported to predict treatment outcome in RA patients when measured in bulk T cells. Furthermore, several of the genes, including STAT3, annotated to the significant CpG sites are relevant for RA susceptibility or the action of MTX. Conclusion We detected CpG sites that were associated with MTX treatment in CD4+ naïve and memory T cells isolated from RA patients. Several of these sites overlap genetic regions previously associated with RA risk and MTX treatment outcome.